Academic Administration Based on the Four Iddhipada Principles of School Administrators In Nong Kung Si District, Kalasin Province - Jitsom, Chantamas; Mahahing, Prachitr; Chotivungso, Phrakhrupalad Boonchuay (Journal of Graduate MCU KhonKaen Campus, 2026)
This research aimed 1) to study the current conditions and the desirable conditions of academic administration based on the Four Iddhipda principles of school administrators in Nong Kung Si District, Kalasin Province; 2) to assess the essential needs in academic administration based on the Four Iddhipda principles of school administrators in Nong Kung Si District, Kalasin Province; and 3) to propose guidelines for academic administration based on the Four Iddhipda principles of school administrators in Nong Kung Si District, Kalasin Province. This study employed a mixed-methods approach, combining quantitative and qualitative research. For the quantitative component, a questionnaire was used as the data collection instrument, with an overall reliability coefficient of 0.91. The sample group consisted of 179 participants, including school administrators and heads of work units. The statistics used included frequency, percentage, mean, standard deviation, and essential needs index. For the qualitative component, interviews were used for data collection with seven experts selected through purposive sampling. The findings of the research were as follows: 1. The current condition of academic administration based on the Four Iddhipda principles of school administrators in Nong Kung Si District, Kalasin Province, was at a high level overall, while the desirable condition was at the highest level. 2. The most essential and urgent need requiring development was curriculum development based on the Four Iddhipda principles, whereas the least was the development of learning processes based on the Four Iddhipda principles. 3. The guidelines for academic administration based on the Four Iddhipda principles of school administrators are as follows: (1) curriculum development grounded in perseverance and determination, focusing on systematic development of teachers and learning; (2) creative and safe use of media and technology; (3) assessment and evaluation that emphasize learner development; (4) educational supervision that promotes collaborative learning; and (5) development of learning processes that emphasize learner-centered approaches.